RETURN SAHAM: MANAJEMEN LABA DAN FAKTOR LAINNYA - MICHELLE METASARI; AAN MARLINAH (E-Jurnal Akuntansi TSM, 2021)
The objective of this research is to test and investigate factor-factor that affect to stock return towards cumulative abnormal return on the listed manufacturing companies in Indonesia Stock Exchange. The population of this research is manufacturing company that listed in the Indonesia Stock Exchange from 2012 until 2015. The samping technique used in this research is purposive sampling. The sample consists of 92 manufacturing companies. This research uses multiple linear regression as the statistical analysis method. The data type is secondary data consists of audited financial statements collected from IDX website.The result of this research show that earning management, audit quality, profitability, leverage, firm size, net profit margin, current ratio, debt to equity ratio, price to book value ratio, and price to earning ratio no influence to stock return which audit quality as a moderating variable between earnings management and stock return show the same result, there is no moderating influence between earning management and stock return relationship.